Identification and optimisation of 4, 5-dihydrobenzo[1, 2-d:3, 4-d]bisthiazole and 4, 5-dihydrothiazolo[4, 5-h]quinazoline series of selective phosphatidylinositol-3 kinase alpha inhibitors. Issue 17 (1st September 2015) - Fairhurst, Robin A.; Gerspacher, Marc; Imbach-Weese, Patricia; Mah, Robert; Caravatti, Giorgio; Furet, Pascal; Fritsch, Christine; Schnell, Christian; Blanz, Joachim; Blasco, Francesca; Desrayaud, Sandrine; Guthy, Daniel A.; et al.
Graphical abstract